A GWO-P&O Algorithm MPPT for PV Systems Under UIC and PSC - Muyassar Muyassar; Tarmizi; Yuwaldy Away (Jurusan Teknik Elektro Universitas Andalas, 2022)
The operation of PV systems can experience uniform (UIC) and partial insolation (PSC) that depends on its environment. Many MPPT algorithm has been proposed in literature such as P&O, and many metaheuristics algorithm such as PSO and GWO. Those algorithm only work at a certain environmental condition. The P&O algorithm only work at UIC but fail to track maximum power at PSC hence reducing efficiency of MPPT system when it is experiencing UIC and PSC. The GWO algorithm can track maximum power at PSC but when the change of insolation to UIC can shift power output below maximum power hence reducing efficiency of MPPT system. In this paper another method is proposed by implementing the result of GWO to the input of the P&O algorithm subsequently the GWO is reset periodically to search a new maximum power point to anticipate any environmental changes. This new method is called a GWO-P&O algorithm. Simulation results show that the GWO-P&O algorithm yields better efficiency compared to the GWO or the P&O algorithm in case the modules of PV array experiencing UIC and PSCs. Simulation is done using MATLAB/SIMULINK software.